2019
DOI: 10.1073/pnas.1903401116
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Kv2.1–syntaxin molecular interaction identifies a first-in-class small molecule neuroprotectant

Abstract: The neuronal cell death-promoting loss of cytoplasmic K+ following injury is mediated by an increase in Kv2.1 potassium channels in the plasma membrane. This phenomenon relies on Kv2.1 binding to syntaxin 1A via 9 amino acids within the channel intrinsically disordered C terminus. Preventing this interaction with a cell and blood-brain barrier-permeant peptide is neuroprotective in an in vivo stroke model. Here a rational approach was applied to define the key molecular interactions between syntaxin and Kv2.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 59 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…Previous preclinical studies from our laboratory have shown efficacious neuroprotection in vivo by targeting the Kv2.1-syntaxin interaction ( fig. S7B), which is the final step in proapoptotic Kv2.1 membrane insertion (9,11). The results in the present study target this process via a completely novel approach, namely, the elimination of the putative insertion sites for cell death trafficking of channels, the Kv2.1 membrane cluster domains.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous preclinical studies from our laboratory have shown efficacious neuroprotection in vivo by targeting the Kv2.1-syntaxin interaction ( fig. S7B), which is the final step in proapoptotic Kv2.1 membrane insertion (9,11). The results in the present study target this process via a completely novel approach, namely, the elimination of the putative insertion sites for cell death trafficking of channels, the Kv2.1 membrane cluster domains.…”
Section: Discussionmentioning
confidence: 88%
“…TBOA is a glutamate transporter inhibitor that produces a slow excitotoxic injury via prolonged N-methyl-d-aspartate (NMDA) receptor stimulation (26). This induces a pronounced potassium current surge mediated by Kv2.1, culminating in delayed apoptotic cell death, mimicking the excitotoxic conditions present in the ischemic penumbra following stroke (9,11,14,26).…”
Section: Tat-dp-2 Prevents Enhancement Of Kv21-mediated Proapoptoticmentioning
confidence: 99%
“…As glutamate can also generate the production of reactive oxygen species via NMDA receptor activation (Reynolds and Hastings, 1995), by simultaneously measuring calcium and zinc transients in neurons (Figure 10), the Reynolds laboratory provided unequivocal evidence that NMDA receptor stimulation leads to a calcium-dependent production of free radicals, both cytoplasmic and mitochondrial in origin, which, in turn, led to the liberation of intracellular zinc (Dineley et al, 2008). This finding, and subsequent work by us and other groups (Granzotto and Sensi, 2015;Yeh et al, 2017Yeh et al, , 2019, provided a critical link between excitotoxic processes and intracellular liberated zincdependent cell injurious signaling cascades. Zinc translocation from presynaptic, zinc containing terminals to postsynaptic cells via calcium-permeable channels (Sensi et al, 1999a,b) can, under FIGURE 10 | Simultaneous detection of glutamate-induced intracellular calcium and zinc in neurons.…”
Section: Linking Excitotoxic Stimuli Intracellular Zinc Release Andmentioning
confidence: 89%
“…This has been, admittedly, a very difficult problem, to which large amounts of financial resources and numerous careers have been devoted. Our own recent work points to new therapeutic avenues to pursue, targeting Kv2.1-mediated potassium efflux in cell death processes ( Yeh et al, 2017 , 2019 ; Schulien et al, 2020 ). Although ameliorating excitotoxic injury and clinical disability has been very challenging, a better appreciation of critical mechanisms can only improve the potential to succeed in addressing this important unmet medical need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation